2023
DOI: 10.1037/tra0001344
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to young people seeking help for trauma: A qualitative analysis of Internet forums.

Abstract: Objective: Exposure to trauma is common in childhood and adolescence and is associated with significant psychopathology. Despite being amenable to treatment, many young people suffering traumarelated distress do not disclose or seek help. Multiple barriers to young people help seeking for mental health concerns have been identified, but very little research has focused on help seeking after trauma exposure. We undertook a qualitative analysis of Internet forums in which young people discuss trauma, aiming to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This study showed that several young people exposed to childhood trauma turned to health care services for help with pain relief. This group often refrains from seeking psychosocial treatment regardless of high needs, 67 , 75 and the assessment of trauma exposure in young people seeking professional help with pain management could be the first step in providing trauma-specific health care to trauma-exposed individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that several young people exposed to childhood trauma turned to health care services for help with pain relief. This group often refrains from seeking psychosocial treatment regardless of high needs, 67 , 75 and the assessment of trauma exposure in young people seeking professional help with pain management could be the first step in providing trauma-specific health care to trauma-exposed individuals.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 Several barriers are at play, such as stigma, a lack of knowledge about mental health and mental health services, a preference for self‐reliance, feeling unworthy of help, concerns about confidentiality and fear of a negative response after disclosure. 7 , 8 , 9 , 10 , 11 , 12 Even if these internal barriers are overcome, pathways to care are complex due to multiple help‐seeking contacts (with general practitioners, emergency services, etc.) and long waitlists, sometimes resulting in a delay of appropriate care.…”
Section: Introductionmentioning
confidence: 99%